Estudo teórico-experimental de tubos de calor assistidos por gravidade para aplicações em coletores solares - Silveira, Igor Cavalcanti da (2019)
Heat pipes are extremely efficient devices capable of carrying high rates of thermal energy over long distances with low temperature drop. For these reasons, over the years, studies have been conducted to introduce them in solar collectors in order to improve the performance of these equipments. However, there are still few applications of heat pipe solar collectors in Brazil. Therefore, for the development of this work gravity assisted heat pipes or wickeless heat pipes (called thermosyphons) were made and underwent a series of laboratory tests that simulated conditions to which solar collectors are subjected when they are exposed to ambient solar radiation, in other words, the devices were subjected to variable heat fluxes with values around 1000 W/m². Two mathematical models were developed to estimate the operating temperature of the system. The concentrated model was based on energy balance and NUT-effectiveness method for heat exchangers. The other elaborated model used the heat diffusion equation for the conduction process that occurs in the tube wall in the evaporator region. The solution was made using the Generalized Integral Transformed Technique (GITT) for steady state operating conditions. In this sense, the theoretical results were compared with the experimental data collected and in general the obtained solutions were satisfactory. Moreover, with the temperature profiles obtained from the experiments conducted it was possible to evaluate the physical phenomena of heat transport as well as to estimate the convective coefficients and define the most appropriate correlations for the thermosyphons developed in this work.